Interpretation of complex phraseological constructions in bilingual phrasal verb dictionaries - Ruzimov, Sh.S (ILIM hám JÁMIYET, 2025)
This study investigates the lexicographic representation of complex phraseological constructions – particularly verb-verb, verb–two-preposition, and verb–adjective combinations – in bilingual phrasal verb dictionaries. Through comparative and descriptive analysis of entries from key publications (e.g., Abdurakhmonova, Erejepova), it identifies inconsistencies in semantic interpretation, syntactic labeling, and typographical presentation, and proposes improvements to enhance clarity and usability for Uzbek learners. The research underscores the need for systematic, theory-informed dictionary design that accounts for idiomaticity, passive/active voice variation, object placement, and grammatical flexibility.